KAJIAN MENGENAI PERAN ASPEK ORGANISASIONAL DAN ASPEK LINGKUNGAN PADA KEPUTUSAN MENGADOPSI TEKNOLOGI INFORMASI - Rahab Rahab (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2009)
Organizational and environment aspects for small businesses have important roles in making decision to adopt information technology (IT). The purpose of this research is examine efect organizational aspects (business size, level of employees’ knowledge IT, information intensity and environment aspects (competitive). A survey was conducted in Yogyakarta city by purposive sampling technique. The samples that are used to data analysing are 102 small business. Partial Least Squares method was used to examine five research hypotheses. Research instrumens validity was measured by convergent validity and discriminant validity. Instrument reliability was measured by cronbach’s alpha and composite reliability. This research shows that firm size, employees’ knowledge about IT, nformation intensity and competitive have significantly positive effect to small businesses decision to adopt IT. This study contributes to insight that organizational and competitive environment aspects effect in making decision to adopt IT.